2020
DOI: 10.3892/etm.2020.8653
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of piRNA expression spectra in a non‑alcoholic fatty liver disease mouse model induced by a methionine‑ and choline‑deficient diet

Abstract: Non-alcoholic fatty liver disease (NAFLD) has become a common health issue worldwide, and P-element-induced wimpy testis (PIWI)-interacting RNAs (piRNAs) have been shown to be differentially expressed in a variety of diseases. The aim of the present study was to investigate the potential relationship between piRNA and NAFLD. A NAFLD mouse model was established using a methionine-and choline-deficient (MCD) diet and methionine-and choline-sufficient (MCS) diet. Following this, mouse liver tissues were removed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Using microarray technology, differential expression of piRNA was reported using liver tissue from NAFDL mice [84]. This study suggested piRNA may have a regulatory role in NAFLD by interacting with proteins involved in several metabolic pathways.…”
Section: Pirnamentioning
confidence: 91%
“…Using microarray technology, differential expression of piRNA was reported using liver tissue from NAFDL mice [84]. This study suggested piRNA may have a regulatory role in NAFLD by interacting with proteins involved in several metabolic pathways.…”
Section: Pirnamentioning
confidence: 91%
“…PiRNAs and PIWI are also abundant in multiple somatic cells, such as in neuronal, liver, exosome, and cancer tissue cells [ 21 , 29 , 34 , 67 ]. The aberrant expression of ectopic piRNAs has been identified across a range of human diseases.…”
Section: The Basic Information Of Pirnasmentioning
confidence: 99%
“…Other ncRNAs such as PIWI-interacting RNAs (piRNAs), small nucleolar RNAs (snoRNAs) and tRNA-derived small RNAs (tsRNAs), have attracted widespread attention in recent years. For instance, some studies have revealed that piRNAs were abnormally expressed and might play a regulatory role in liver cancer, non-alcoholic fatty liver disease and liver injury[ 156 - 158 ]. Moreover, snoRNAs and tsRNAs are involved in several liver diseases as biomarkers and therapeutic targets[ 159 - 162 ].…”
Section: Additional Ncrnasmentioning
confidence: 99%